Peran Media Sosial Dalam Peningkatan Partisipasi Pemilih Pemula Pilkada 2024 Di Kecamatan Galesong Kabupaten Takalar - Sukmawati Syam; Ihyani Malik; Riskasari (Universitas Muhammadiyah Makassar, 2026)
This study aims to determine the role of social media in increasing the participation of first-time voters in the 2024 regional elections in Galesong District, Takalar Regency. The research method used was a qualitative case study approach. Data were collected through observation, interviews, and documentation. Data analysis was conducted using thematic analysis techniques. The results indicate that social media plays a strategic and significant role in encouraging first-time voter participation. First, from a social contact perspective, social media has proven successful in creating a dynamic interaction space, both directly and indirectly, between first-time voters and fellow voters and election organizers. Second, social media communication serves as a highly effective means of conveying election information. The Takalar Regency General Elections Commission (KPU) successfully utilized digital platforms to disseminate informative and engaging content, enabling first-time voters to quickly and accurately access candidate data, programs, and election schedules. Third, awareness of the role of social media plays a role in increasing first-time voters' understanding of their rights and responsibilities in the democratic process.